EXPLORING THE CORRELATION OF SOCIOLINGUISTIC COMPETENCE AND SPEAKING PROFICIENCY, AND HOW LEARNERS PERCEIVED THEM - Fariha, Nur; Anwar, Khoirul; Maruf, Nirwanto (University of Kuningan, 2023)
This study aims to explore the correlation between sociolinguistic competence and speaking proficiency in language learners while examining their perceptions of these aspects. Conducted using a mixed-methods approach, the research gathered data from 65 participants across multiple universities in Lamongan Regency, East Java, Indonesia. Quantitative analysis involved Test of English as a Foreign Language (TOEFL) scores, structured surveys, and questionnaires assessing sociolinguistic competence. Qualitative insights were obtained from in-depth interviews, illuminating participants' experiences, beliefs, and challenges in diverse social settings related to language use. Quantitative findings indicate a strong correlation between sociolinguistic competence and speaking proficiency. The Pearson correlation coefficient for